IMPLEMENTASI STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART AND MATHEMATICS) DALAM PEMBELAJARAN ABAD 21 - Iim Halimatul Mu'minah; Yeni - Suryaningsih (Universitas Majalengka, 2020)
ABSTRACTThe 21st century world of work requires workers to have mastery in science and technology as well as a variety of communication skills, critical thinking, creativity and collaborative abilities. Science learning especially in Indonesia in general has not directed students to master these skills. For this reason, it is necessary to develop learning that is able to integrate Science, Technology, Engineering, Arts and Mathematics through STEAM Implementation in this 21st century learning. STEAM learning is able to increase students 'academic mastery as well as implementing it in students' daily lives so it is hoped that through STEAM learning, students are able to practice 21st century skills. STEAM Implementation in Learning is the process of applying ideas, ideas, and concepts contained in the meta discipline of science in a learning that is expected to improve abilities both in the cognitive, affective and psychomotor aspects of students in the face of technological progress. This research discusses how the implementation of STEAM in 21st Century learning, specifically science learning. This study aims to provide benefits related to STEAM (Science, Technology, Engineering, Arts and Mathematics and its Implemenlation in the 21st Century learning, especially science learning in schools, both teachers and lecturers as instructors.Keywords: Implementation, STEAM, 21st Century Learning.